Kahit isang saglit - Perez, Gilbert; Sineneng, Jerry Lopez (ABS-CBN Production, 2003)
A brush with a powerful drug syndicate brings together the lives of Rocky Santillan (Jericho Rosales) and Garie Hang-Li (Carmen Soo), and this near death experience makes them fall for each other deeply. Soon they will realize that despite their disparate cultures they share a deep attachment to their families which motivates all of their actions: Rocky, an agent of the Philippine Drug Enforcement Agency whose commitment to his job is inspired by his desire to give justice to his father's death which he witnessed as a child. and Garie, an heiress of a cargo empire in Malaysia, whose only dream in life is to be reunited with her estranged Filipino father. But their love story is thwarted by yet another force: Garie's grandmother Popong, who set her up for an arranged marriage with shipping mogul Amir Mohammed to save their own company. The sudden turn of events makes Garie unable to fulfill her promise of going to the Philippines with Rocky, and it is only when Garie's mother Eunice helps her flee that their love is given another chance.